Profile Analysis of Students' Problem-Solving Abilities on ImpulseMomentum Physics Material - Millah, Roprop Latiefatul; Malik, Adam; Chusni, Muhammad Minan (UIN Fatmawati Sukarno Bengkulu, 2022)
The potential possessed by students is not only contextual. However, it must be comprehensive and essentially understand the concept of science. Based on the results of a preliminary study conducted at SMAN 2 Garut using interview techniques with Physics teachers, it was revealed that students' learning in schools had implemented various learning models. The achievement of learning outcomes from each learning model is different depending on how the implementation of the learning model is carried out by adjusting the appropriate learning materials. Characteristics of students who are different in the class cause various student responses to differ from the learning model. The average student learning achievement in the aspect of problem-solving at the school for physics is 22% overall. The learning model will be judged appropriate for the material if, in the delivery of learning materials, students can achieve appropriate learning objectives and with certain aspects of the learning component by using indicators of achievement of certain aspects. Students' problem-solving ability in learning Physics subjects has difficulty because students' understanding of learning materials is only theoretical and focused on problem-solving through various formulas or equations in Physics learning materials. Initiating learning with various active learning models with various stimuli and involving student participation makes it easier for students to understand learning materials. The highest answer analysis on problem description questions is 26.5625% with the lowest and lowest criteria on the assessment of the logical procession aspect of 12% which represents the student's problem ability profile is still low on this material.